DAYS OPEN PADA SAPI PERAH IMPOR DI BBPTU-SP BALAI BESAR PEMBIBITAN TERNAK UNGGUL SAPI PERAH) BATURRADEN - , ROHMATUL HARTINI, Dr. drh. Prabowo Purwono Putro, M.Phil. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study was conducted to know the reproductive parameters especially days open of the dairy cow of BBPTU-SP Baturraden. Total number of primiparous dairy cows were 102 heads. Data attained from the log books then analyzed and calculated. The result of study that Days open of dairy is 82.99+9.86 days